Macular volume and fovea thickness as OCT-criteria for multiple sclerosis. Preliminary results - M. E. Konovalov; M. L. Zenina; K. V. Burdel; M. M. Konovalova (Acta Biomedica Scientifica, 2021)
Background. The characteristic optical coherence tomography (OCT) changes in the optic nerve head in patients with multiple sclerosis are known and have been described many times, however, the state of the macular area is described in a small number of publications.The aim: to analyze the changes in the macular area of the retina in patients with multiple sclerosis, to identify the OCT signs pathognomonic for this disease and to trace their changes over time as the disease progresses.Material and methods. In addition to the standard ophthalmological examination, 28 patients (55 eyes) diagnosed with multiple sclerosis underwent OCT of the macular zone to determine the thickness of the fovea and the volume of the macula in the 6 mm zone. The follow-up period was 6–12 years. The endpoints were the primary treatment and the most recent inspection.Results. At the initial examination, the visual acuity was 0.96 ± 0.24 (95% CI: 0.9–1.03), fovea thickness – 253.0 μm (Q1–Q3: 233.0–264.0), macular volume – 5.471 mm3 (Q1–Q3: 5.281–5.625). In 37 cases (67.3 %), the macular volume was below normal. The initial fovea thickness was below normal in 9 cases (16.4 %). At the end of the study, visual acuity did not change statistically (p = 0.824) and amounted to 0.96 ± 0.25 (95% CI: 0.90–1.04). The fi nal thickness of the fovea was 247.5 μm (Q1–Q3: 233.0–260.0), changes are statistically significant (p = 0.02). Number of cases with a thickness below normal in the fi nal study was 11 (20 %), change of frequency of cases was not statistically signifi cant (p = 0.5). The fi nal macular volume was 5.393 mm3 (Q1–Q3: 5.197–5.565), the changes are statistically significant (p = 0.023). The final number of cases with a volume below the norm was 42 (76.4 %), the change in the frequency of cases is close to statistically signifi cant (p = 0.063). At all stages of the study, there was no case of an isolated decrease in the thickness of the fovea without a decrease in the volume of the macula.Conclusion. The decrease in the volume of the macula with time while maintaining the thickness of the fovea within the normal range can be attributed to the pathognomonic OCT signs of multiple sclerosis. This criterion can be used for a comprehensive assessment of the course and therapy of this disease.